Adoção ou não? Eis a questão! Adoção da inovação e competitividade na micro e pequena empresa : uma análise no contexto da crise ocasionada pela COVID-19 - Campos, Juliana Alves (2022)
The objective of this work is to identify the relationships between the adoption of innovations in organizations and the competitiveness of MSEs (Micro and Small Enterprises), during the Covid-19 pandemic period, through the perspective of Rogers' organizational model (2003). To achieve this purpose, four research hypotheses were suggested: hypothesis 1 (H1) - there is a positive relationship between the adoption of innovations in organizations and the competitiveness of MSEs in the pandemic period; hypothesis 2 (H2) – there is a positive relationship between the leader's characteristics and the adoption of innovations in organizations; hypothesis 3 (H3) – there is a positive relationship between the performance of the internal organizational structure and the adoption of innovations in organizations; and hypothesis 4 (H4) – there is a positive relationship between the performance of the organizational external environment and the adoption of innovations in organizations. As a research method, a descriptive study of a quantitative nature was carried out with 162 micro and small entrepreneurs in the food segment, in the period between September 2021 and January 2022. Structural Equations, the latter based on Partial Least Squares - PLS (Partial Least Square). The results found allow us to conclude that, for the 162 managers consulted, the performance of the internal organizational structure (centralization, complexity, formalization, interconnectivity, organizational slack and size) is the variable that has the highest correlation with the organization's decision, with regard to adoption of innovations in the pandemic. In addition, respondents pointed out that the adoption of innovations in the organization has a strong correlation with the competitiveness of MSEs, in the Covid-19 pandemic, reinforcing the importance of adopting innovations for the competitiveness of small companies against their competitors, especially at a time of crisis. As contributions, this research: (a) expands the analysis of the attributes suggested by Rogers (2003) to the scope of MSEs and relates them to competitiveness in the pandemic; (b) provides a model and validated instrument that can be replicated in other phenomena; (c) strengthens the theoretical basis of the field of innovation and strategy; (d) it presents subsidies to understand the adoption of innovations as a strategy for competitiveness in the period of crisis caused by the covid-19 pandemic. (e) highlights the importance of investing in the adoption of innovation as a way of maximizing profit, enhancing competitiveness and expanding business; (f) to investors, it provides guidance as to the factors that are essential for the marketing of their products in the food industry MSEs in Aracaju.